Dampak Psikologis Akibat Covid-19 pada Masyarakat Indonesia - Desi Wahyu Susilowati (UNS Press, 2021)
Covid-19 or Corona Virus Disease become an outbreak for the world, including Indonesia. People have been doing something to prevent Covid-19. Quarantine, social distancing, and keeping healthy is the government program to reduce the spread of Virus. This condition gives impact for everyone especially in psychology. This research aims to find correlation distress and obsessive compulsive disorder for pandemic. This research is quantitative research with correlational methods. The data have been collected from 157 subjects who are over twenty years old with distress and obsessive compulsive disorder scale. Data analysis method used is the product moment correlation from Pearson. The result showed that sign (0.000)